Merdeka Belajar Curriculum Innovation and Its Application in Education Units - Dini Irawati; Hakin Najili; Supiana Supiana; Qiqi Yuliati Zaqiah (Universitas Muhammadiyah Enrekang, 2022)
This article aims to describe one of the innovations in the field of curriculum, namely the independent curriculum which is the policy of independent learning episode fifteenth episode. The method used by the author is library research on various studies related to the independent curriculum. This curriculum is applied as a form of government response in this case kememdikbudristek to pandemic conditions that result in loss learning conditions or as a recovery curriculum. The strategy for implementing the independent curriculum implemented by the government is not carried out in a masiv basis, but is adjusted to the readiness and conditions of each educational unit. In the 2022/2023 school year, the Government provides options for all educational units in implementing the curriculum, namely the independent curriculum, the emergency /simplified curriculum or the 2013 curriculum. The target of piloting this independent curriculum is as many as 2500 driving schools spread across 34 provinces. Limited tests conducted on driving schools aim to get feedback as curriculum improvement material. The results obtained include showing that schools flexibly and creatively can be given the flexibility to design and carry out learning in accordance with students' abilities. This curriculum change will be successful if supported by changes in the mindset of educators and education personnel and other educational stakeholders.